2013
DOI: 10.1021/ie403378w
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Carbon Nanotube and Polyethersulfone on Flame Retardancy of Carbon Fiber Reinforced Epoxy Composites

Abstract: By using resin transfer molding (RTM) technology, carbon fiber (CF) reinforced epoxy composites (CF/Epoxy, CF/PES/Epoxy, and CF/PES-MWCNT/Epoxy) are prepared. CF is the reinforced fiber, Epoxy is the epoxy matrix, and PES-MWCNT is the multiwall carbon nanotubes doped polyethersulfone film. Their fire behavior is systematically studied according to limiting oxygen index (LOI), vertical burning test (UL94), and cone calorimeter test (CCT). Their thermal degradation process, kinetics, and flame retardant mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…47 The LOI provides an efficient measure of flammability for polymer materials over broad ranges. Figure 9 provides the HRR and THR versus time curves of selected samples, the related data and LOI values are summarized in Table 4.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…47 The LOI provides an efficient measure of flammability for polymer materials over broad ranges. Figure 9 provides the HRR and THR versus time curves of selected samples, the related data and LOI values are summarized in Table 4.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…To reduce the flammability of epoxy thermosets according to the demands of electronics and electrical engineering, a great number of studies have been carried out . Several works focused on reactive flame retardants, incorporating the flame retarding unit into the thermoset network to form an intrinsically flame retardant molecular chemical structure.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the control CFRP, both CFRP@Mat EG‐GF and CFRP@Mat EG‐GF‐MW had an obvious reduction of PHRR values by 46.3 and 94.1%. As shown in Figure (a), the CFRP exhibited one broad peak HRR at 130 s, which showed that the char was not compact enough to hinder the sustained flame . However, for CFRP@Mat EG‐GF , it exhibited two peaks at 130 and 230 s with HRR values of 146.4 and 126.01 kW/m 2 , the second peak of HRR appeared lower and broader than the first one.…”
Section: Resultsmentioning
confidence: 93%